Inkorporacja parafii zdezorganizowanej w Rzeczypospolitej w okresie potrydenckim na przykładzie parafii Słupie i Modliborzyce w diecezji krakowskiej - Szulc, Dominik (Archiwa, Biblioteki i Muzea Kościelne, 2016)
A case study of the parishes of Słupie and Modliborzyce allows us to analyze in detail the process of the territorial, and administrative (functional) and material incorporation of the parish located in the Republic of Poland during the post-Tridentine period. It highlights the causes of this process, gives an insight into the process, and finally enables us to analyze the obstacles that affect the rate of incorporation. Thanks to it, we can evaluate how the separateness of the parish intended for incorporation was liquidated, and we can also describe the functioning of the parish in the specific meantime, i.e. between the moment when the territorial incorporation was done and ongoing process of the material incorporation, when the new parish was characterized by a certain dualism in functioning. The territorially uniform parish, which was under the process of incorporation, functioned then with the active use of buildings of the non-existent parish, which was formally incorporated. Therefore, the incorporation of the parish appears to us as the long lasting and multistage process. In the case of Słupie and Modliborzyce, it lasted from the mid-17th to the late 18th century, and the first signs of disorganization in the parish of Słupie can be observed at least at the end of the 16th century. The half of the 16th century marks the erection of the parish in Modliborzyce, then, a few years later, the liquidation of the independence of the parish of Słupie and its territorial incorporation into the parish of Modliborzyce. Nevertheless, transferring residential and economic functions lasted for nearly 200 years; the last parish buildings in Słupie were demolished at the end of the 19th century.